Article 9 Water Framework Directive: What does the term "water services" mean? On the EU Court of Justice conclusions of Advocate General Jääskinen in case C-525/12 - Erik Gawel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
The conclusions of Advocate General Jääskinen in the matter of the infringement proceedings against Germany, regarding the scope of the term "water services" in Article 9 of the Water Framework Directive, are now available. In these he considers that the action brought by the Commission against the narrow interpretation in Germany, which is restricted to water supply and waste water disposal, is inadmissible due to the fact that there is no complaint in respect of any clearly defined conduct that would constitute an infringement; in the alternative he materially agrees in full with the position put forward by Germany. However, this paper argues that the AG's main arguments in favour of a strict interpretation are misleading.
Keywords: 330